Interactive map of Participatory Models for Biodiversity Conservation - CGIAR Research Program on Policies, Institutions, and Markets (2019)
This tool is at proof of concept stage. Developing a more nuanced characterization of participatory approaches is a fundamental first step for identifying what works, where and under what conditions in a subsequent phase of this research.